Biological diversity of freshwater fishes in small streams in Peninsular Malaysia - Amirrudin Ahmad (Scotland : University of St Andrews, 2012)
Peninsular Malaysia has a diverse flora andfauna, much of which is yet to be documented. The freshwater fishes are one important group that have received little attention. Accordingly, the overarching goal of my study is to investigate the pattern of species richness and analyse the community composition and assemblage structure of fishes in the small streams in Peninsular Malaysia.